Association of bifid epiglottis and laryngeal web with Bardet-Biedl syndrome: A case report. (July 2019) - Poulin, Marc-Antoine; Laframboise, Rachel; Blouin, Marie-Julie
Abstract: Bardet-Biedl syndrome (BBS) is a rare autosomal-recessive disease characterized by rod-cone dystrophy, obesity, postaxial polydactyly, cognitive impairment, hypogonadism and renal abnormalities. Bifid epiglottis and anterior laryngeal web are rare congenital anomalies and are often constituent of polymalformation syndromes. We report a case of a 9-month-old patient initially referred in otolaryngology (ENT) for dysphonia and recurrent respiratory infections. Physical exam and fiberoptic nasopharyngolaryngoscopy showed bifid epiglottis and laryngeal web associated with BBS. Those laryngeals anomalies may be underdiagnosed in BBS and this case supports the importance of upper airway evaluation by an ENT team, especially with respiratory symptoms or dysphagia.